Genética das populações do sauim-de-coleira (Saguinus bicolor - Callitrichidae) em fragmentos florestais e floresta contínua: implicações para conservação - Santos, Wancley Garcia (Instituto Nacional de Pesquisa da Amazônia - INPA, 2005)
In the urban forest fragments of Manaus one finds the endemic pied-faced tamarin (Saguinus bicolor) which is considered the most endangered callitrichid primate of the Amazon; it is listed in the appendix I of CITES and is classified by IUCN as critically endangered and in danger of extinction . The present study reports the result of a genetic survey of the pied-faced tamarin from four forest fragments of Manaus: UFAM (in existence since ±15 years), SESI (in existence since ±12 years), Cidade Nova (in existence since 5-6 years), and a population of the Reserva Adolfo Ducke which borders Manaus on two of its sides. Historically these fragments were connected, and it is also believed that the SESI population was exterminated during the fragmentation process, and at a later date the SESI region was recolonized most probably by individuals from UFAM. Because of its precarious situation caused by the rapid growth of Manaus, a study to evaluate patterns of distribution of genetic diversity of this species is important for conservation planning. Conservation of genetic diversity is important for the pied-faced tamarin as for other species since the loss of genetic diversity may increase risk of extinction and diminish potential of future adaptations. Genetic profile was assessed by nine microsatellite markers in DNA samples obtained from hair and skin biopsy samples of 95 individuals. Genotypes were resolved on the MegaBase automatic sequencer, and binned in the program Genetic Profiler. Total number of polymorphic alleles detected per locus in all samples analyzed varied from 3 to 22 alleles. An average number of alleles per locus per population varied from 3.4 to 6.7. Average populational heterozygosity estimated from all loci ranged from 0.59 to 0.68. Analyses employing the parameter M (obtained from the program M value ) which tests for recent reduction in effective population size a bottleneck test indicated that the UFAM and SESI populations experienced a significant reduction in effective population size. Cidade Nova, the most recently fragmented region, showed a non-significant reduction after Bonferroni correction for multiple comparisons, however, it was close to the cut-off value (P = 0.046). The Reserva Adolfo Ducke biological station is connected on two sides to a continuous forest, and it appeared not to be significantly affected by fragmentation. Significant reductions in effective population sizes were directly related with the length of time the forest fragments were isolated. Levels of genetic diversity observed in the pied-faced tamarin groups inhabiting these forest fragments were considered moderate in comparison to other primates. These results are encouraging for the conservation and management, including reintroductions and translocations, of this primate species inhabiting the urban forest fragments of Manaus.
Keywords: Saguinus bicolor; calitriquídeos; microssatélite; variabilidade genética; DNA nuclear